An image dithering via Tchebichef moment transform - Abu, Nur Azman; Ernawan, Ferda; Herman, Nanna Suryana (Science Publications, 2013)
Many image display applications and printing devices allow only limited number of colours. They have limited computational power and storage to produce high quality outputs on high bit-depth colour image. A dithering technique is called for here in order to improve the perceptual visual quality of the limited bitdepth images. A dithered image is represented by a natural colour in the low bit depth image colour for displaying and printing. This technique obtains low cost colour image in displaying the colour and printing image pixels. This study proposes the dithering technique based on Tchebichef Moment Transform (TMT) to produce high quality image at low-bit colour. Earlier, a 2´2 Discrete Wavelet Transform (DWT) has been proposed for better image quality on dithering. The 2´2 TMT has been chosen here since it performs better than the 2´2 DWT. TMT provides a compact support on 2´2 blocks. The result shows that 2´2 TMT gives perceptually better quality on colour image dithering in significantly efficient fashion.